Jahn-Teller distortion driven magnetic polarons in magnetite - H. Y. Huang (Nature Portfolio, 2017)
The Verwey transition of magnetite is complex due to the coexistence of strong correlations and electron-phonon coupling. Here, the authors use resonant inelastic X-ray scattering to show evidence for magnetic polarons in magnetite and provide insight into the nature of the transition.